Slug days - Leach, Sara, 1971- (Pajama Press Inc., 2017)
Seeing the world very differently because of her Asperger Syndrome, young Lauren struggles to navigate the challenges of school life and masters tricks to stay calm, understand others' feelings and let her personality shine. By the award-winning author of Count Me In.